Penerapan Teori Patricia Benner dalam Proses Kredensial Keperawatan Ditinjau dari Sudut Pandang Filosofi di Rsud Kota Dumai - Junaina Ridwan; Siti Rahmalia Hairani Damanik (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Nursing credentials are a formal system that aims to assess and recognize the competence of nursing staff in providing care that meets professional standards. This process is not only legal and administrative, but also reflects the level of expertise and professional responsibility of a nurse. Objective: to analyze and understand the application of Patricia Benner's Theory philosophy of